The allostery model of TCR regulation - Schamel, Wolfgang; Höfer, Thomas (The journal of immunology, 2017)
The activity of the αβ TCR is controlled by conformational switches. In the resting conformation, the TCR is not phosphorylated and is inactive. Binding of multivalent peptide-MHC to the TCR stabilizes the active conformation, leading to TCR signaling. These two conformations allow the TCRs to be allosterically regulated. We review recent data on heterotropic allostery where peptide-MHC and membrane cholesterol serve opposing functions as positive and negative allosteric regulators, respectively. In resting T cells cholesterol keeps TCRs in the resting conformation that otherwise would become spontaneously active. This regulation is well described by the classical Monod-Wyman-Changeux model of allostery. Moreover, the observation that TCRs assemble into nanoclusters might allow for homotropic allostery, in which individual TCRs could positively cooperate and thus enhance the sensitivity of T cell activation. This new view of TCR regulation will contribute to a better understanding of TCR functioning.
Gesehen am 11.04.2018